2020
DOI: 10.3390/pathogens9110953
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Avian Influenza Viruses in Domestic Ducks at the Waterfowl-Chicken Interface in Wetlands

Abstract: Ducks are a natural reservoir of influenza A viruses (IAVs) and can act as a reassortment vessel. Wetlands, such as Hakaluki and Tanguar haor in Bangladesh, have unique ecosystems including domestic duck (Anas platyrhynchos domesticus) rearing, especially household and free-range ducks. A cross-sectional study was, therefore, conducted to explore avian influenza status and its distribution and risk factors in the wetland areas. During the three consecutive winters of 2015–2017, specifically in December of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…According to the findings of this study, backyard poultry flocks are not exempted from avian influenza exposure. Studies by [ 52 , 53 ] also found AIV in backyard poultry in Bangladesh. In addition, we found that chickens and waterfowl raised in backyards have been exposed to multiple subtypes of AIV.…”
Section: Discussionmentioning
confidence: 94%
“…According to the findings of this study, backyard poultry flocks are not exempted from avian influenza exposure. Studies by [ 52 , 53 ] also found AIV in backyard poultry in Bangladesh. In addition, we found that chickens and waterfowl raised in backyards have been exposed to multiple subtypes of AIV.…”
Section: Discussionmentioning
confidence: 94%
“…From multivariable analysis, we found that the presence of waterfowl in the vendor shop increases the risk of AIV in pigeons and quail. There is ample evidence that influenza viruses were spread from waterfowl to commercial poultry and pet birds (42). Ducks are regarded as the AIV virus's 'Trojan horse' (43)(44)(45).…”
Section: Aiv Virus and Associated Factorsmentioning
confidence: 99%
“…Thus, ducks are considered to play a key role in transmitting the virus, with a potential consequence of disease in domestic poultry [18,19]. Ducks are known as the waterfowl reservoir of AIV and may play an important role in spreading AIV infection worldwide [15,18,20]. Other risk factors observed in our study were keeping ducks and geese in the markets for sales.…”
Section: Discussionmentioning
confidence: 86%